2021
DOI: 10.1161/circ.144.suppl_1.10550
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 10550: Mental Health Disorders and Readmissions Following Acute Myocardial Infarction

Abstract: Introduction: Hospital readmissions following an acute myocardial infarction (AMI) are associated with increased mortality and morbidity. The association of mental health disorders (MHD) and risk of readmission following AMI is not well studied. Hypothesis: We hypothesized that among patients with AMI, a co-morbid diagnosis of MHD is associated with increased risk of readmission. Methods: We analyzed the Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…While the prevention of medical complications undoubtedly demands clinical attention, so do the potential psychiatric complications associated with cardiovascular disease (CVD). Depression and anxiety in patients post-MI are consistently associated with adverse health outcomes 5–10 . Nevertheless, in the midst of managing complicated and multifaceted care post-MI, clinicians often overlook mental health concerns due to time constraints and lack of knowledge, leaving patients untreated and at risk 11 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the prevention of medical complications undoubtedly demands clinical attention, so do the potential psychiatric complications associated with cardiovascular disease (CVD). Depression and anxiety in patients post-MI are consistently associated with adverse health outcomes 5–10 . Nevertheless, in the midst of managing complicated and multifaceted care post-MI, clinicians often overlook mental health concerns due to time constraints and lack of knowledge, leaving patients untreated and at risk 11 …”
Section: Introductionmentioning
confidence: 99%
“…It was later found that patients with MI have an additional 50% increased risk of stroke if they experience depression 6 . Mental health disorders, including MDD, are also associated with a higher risk of 30-day readmission after MI and a 1.6% increase in adverse cardiovascular events 7,8 . Post-MI depression is associated with sedentary lifestyles and treatment nonadherence as well 9,10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation